Pengaruh Kompetensi, Motivasi, dan Kreatifitas Terhadap Kinerja Guru Melalui Kepuasan Kerja - Sri Langgeng Ratnasari; Gandhi Sutjahjo; Ervin Nora Susanti; Rona Tanjung; Widodo Ismanto (Manajemen Pendidikan, 2021)
This study was to analyze the effect of competence, motivation, and creativity on teacher performance through job satisfaction. The population of this study was 117 high school teachers in Batam. The sample of this research is 117 samples, with census sampling technique. This research is a quantitative research with SEM analysis technique. The results of the study are: (1) Competence has a significant effect on job satisfaction. (2) Motivation has a significant effect on job satisfaction. (3) Creativity does not have a significant effect on job satisfaction. (4) Competence, Motivation, and Creativity have a significant effect on job satisfaction. (5) Competence has no significant effect on teacher performance. (6) Motivation has a significant effect on teacher performance (7) Creativity does not have a significant effect on teacher performance. (8) Competence, Motivation, Creativity have no significant effect on teacher performance. (9) Job satisfaction does not have a significant effect on teacher performance. The novelty of this research is that creativity has no significant effect on job satisfaction, competence has no significant effect on teacher performance, creativity has no significant effect on teacher performance, competence, motivation, creativity has no significant effect on teacher performance, and job satisfaction has no significant effect on teacher performance. This is different from the research results of previous researchers.